Longitudinal Analysis of Head Coach Turnover of Women’s NCAA D-I Teams - Nicole LaVoi; Hannah Silva-Breen (Journal of Intercollegiate Sport, 2022)
The goal of the current study was to add to existing literature pertaining to occupational turnover of sport coaches through examination of longitudinal data of head coaches of women’s teams in select NCAA Division-I conferences. The current study is the first of its kind, providing longitudinal data to help prove or dispel common narratives about women coaches and illuminate patterns of gender and discrimination. The average rate of head coach turnover of NCAA Division I FBS women’s sport teams is lower than the average rate of employee turnover in the United States. Although encouraging for the entire coaching profession, discriminatory turnover patterns appear to be prevalent. Men in this sample were twice as likely as women to be coaching, regardless of the institutional reason for their departure. When men are fired, they have a greater likelihood to be rehired, especially at the same level and in the same role. Men are also afforded twice the opportunity, as they can in turn coach men, coed, or women, while women are relegated to coaching women or coed teams. Athletic departments and policy makers should use these insights to improve their coach hiring and retention practices